The Effects of Mobile Games on Elementary School Students' Achievement in Aceh - Faizatul Husna; Hanifuddin Jamin; Rizki Juliandi (Jurnal Basicedu, 2022)
Research into mobile game addiction has increased over the previous two decades. The purpose of this study was to investigate the association between on-line mobile gaming and academic performances among adolescent students in Aceh's elementary schools. The study revealed that boys are more of a player compared to girls who often play games and those who play online games are around 11-12 years old have an average playing time 3-5 hours/day. The research population consisted of elementary students from Aceh, with a sample size of 55 pupils. Included in the study was the Game Addiction Scale (Lemmens et al., 2009). Then, using regression analysis, the hypothesis was tested. From the finding, we can conclude that academic performance was found to be negatively associated with online gaming. This is owing to the fact that playing games for long periods of time reduces their ability to focus on academic tasks. This study can serve as a reference to adolescents online gaming habits, which could be a factor affecting their academic achievement.